Independent and combined effects of multiple predators across ontogeny of a dominant grazer. Issue 9 (13th May 2014) - Soomdat, Nicole N.; Griffin, John N.; McCoy, Michael; Hensel, Marc J. S.; Buhler, Stephanie; Chejanovski, Zachary; Silliman, Brian R.
<x xml:space="preserve">Abstract</x> Ecosystems host multiple coexisting predator species whose interactions may strengthen or weaken top–down control of grazers. Grazer populations often exhibit size‐structure, but the nature of multiple predator effects on suppression of size‐structured prey has seldom been explicitly considered. In a southeastern US salt‐marsh, we used both field (additive design) and mesocosm (additive‐substitutive design) experiments to test the independent and combined effects of two species of predatory crab on the survival and predator‐avoidance behavior (i.e. a non‐consumptive effect) of both juveniles and adults of a dominant grazing snail. Results showed: 1) juvenile snails were more vulnerable to predation; 2) consumptive impacts of predators were hierarchically nested, i.e. the larger predator consumed both juvenile and adult snails, while the smaller‐bodied predator consumed only juvenile snails; 3) there were no emergent multiple predator effects on snail consumption; and 4) non‐consumptive effects differed from consumptive effects, with only the large predator inducing predator‐avoidance behavior of individuals within either snail ontogenetic class. The smaller predator therefore played a functionally redundant trophic role across the prey classes considered, augmenting and potentially stabilizing trophic regulation of juvenile snails. Meanwhile, the larger predator played a complementary and functionally unique role by both expanding the size‐spectrum of prey trophic regulation and non‐consumptively altering prey behavior. While our study suggests that nestedness of consumptive interactions determined by predator and prey body sizes may allow prediction of the functional redundancy of particular predator species, it also shows that traits beyond predator body size (e.g. habitat domain) may be required to predict potentially cascading non‐consumptive effects. Future studies of multiple predators (and predator biodiversity) should continue to strive towards greater realism by incorporating not only size‐structured prey, but also other aspects of resource and environmental heterogeneity typical of natural ecosystems.